Accounting for heritage assets: why and how? (Literature study on cultural heritage in Indonesia) - Wiwin Juliyanti; Yohanes K. Wibowo (Penerbit Goodwood, 2020)
Purpose: This study aims to provide an overview related to research on heritage assets in Indonesia. This study classifies and reviews articles based on research methods and focused results regarding accounting treatment, is it in accordance with Government Accounting Standards (SAP)? Research Methodology: This research is a literature study which contains theories that are relevant to the research problem. The data collection is taken from secondary data sources, SAP and various scientific articles. Results: The results demonstrate that the treatment in several heritage assets in Indonesia has referred to the prevailing SAP, historical assets are recorded as fixed assets, without valuation using cost or revaluation, the majority has been presented in the financial report based on accounting principles, this means the government accountability requirements for disclosure of heritage assets have been quite achieved. Limitations: Secondary data sources using several articles that are not all published in accredited journals. Contribution: This research has implications for the government to evaluate the function of financial reporting as an accounting tool that facilitates the realization of transparency and accountability. Keywords: Heritage assets, Recognition, Assessment, Measurement, Presentation and disclosure, PSAP No. 07 of 2010 concerning Accounting for Fixed Assets